2001
DOI: 10.1016/s0893-133x(00)00186-x
|View full text |Cite
|
Sign up to set email alerts
|

Opiate Withdrawal-Induced Fos Immunoreactivity in the Rat Extended Amygdala Parallels the Development of Conditioned Place Aversion

Abstract: Low doses of naloxone have been shown to affect the motivational aspects of opiate withdrawal in morphinedependent rats. Conditioned place aversion to opiate withdrawal is one of the most sensitive of motivational indices of opiate withdrawal and is thought to be mediated by the basal forebrain. Expression of the transcription factor Fos is known to increase during opiate withdrawal, but its presence during low-dose antagonist-precipitated withdrawal has not previously been established. In order to determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
88
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 33 publications
(51 reference statements)
7
88
0
3
Order By: Relevance
“…Thus, naloxone-induced P-CREB in morphine-dependent rats might reflect synergism between signaling from withdrawal-induced glutamate release (Sepulveda et al, 1998) and increased cAMP. Other studies have shown that low doses of naloxone induce c-fos and Fos-related antigens (FRAs) in the NAc of morphinedependent rats (Walters et al, 2000;Gracy et al, 2001). Fos can be activated by Ca 2ϩ -mediated signaling and is not necessarily reliant on P-CREB (Lerea and McNamara, 1993), suggesting different sensitivities and functions for these various proteins.…”
Section: Dissociation Of Motivational and Somatic Withdrawal Signsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, naloxone-induced P-CREB in morphine-dependent rats might reflect synergism between signaling from withdrawal-induced glutamate release (Sepulveda et al, 1998) and increased cAMP. Other studies have shown that low doses of naloxone induce c-fos and Fos-related antigens (FRAs) in the NAc of morphinedependent rats (Walters et al, 2000;Gracy et al, 2001). Fos can be activated by Ca 2ϩ -mediated signaling and is not necessarily reliant on P-CREB (Lerea and McNamara, 1993), suggesting different sensitivities and functions for these various proteins.…”
Section: Dissociation Of Motivational and Somatic Withdrawal Signsmentioning
confidence: 99%
“…Considering that morphine withdrawal increases the function of downstream targets of cAMP signaling in the striatum and NAc (Nye and Nestler, 1996;Gracy et al, 2001;Shaw-Lutchman et al, 2002) and triggers aversive withdrawal signs, we examined whether precipitated morphine withdrawal would activate CREB and GluR1 within the NAc. We also examined whether D 1 agonist-induced stimulation of cAMP signaling during precipitated morphine withdrawal would further increase CREB and GluR1, thereby exacerbating withdrawal signs.…”
Section: Introductionmentioning
confidence: 99%
“…NMDA receptors are present in extensive areas of the central nervous system, including limbic brain areas that are strongly implicated in opioid plasticity (Gracy et al, 2001), particularly the central nucleus of the amygdala (CeA). Electron microscopic immunohistochemical studies indicate that NMDA receptors have a heterogeneous cellular localization in the extended amygdala and other brain areas implicated in opioid dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the increase in the aversive effect of naloxone has been shown to persist for 48 h after morphine administration (Parker et al, 2002), by which time very little morphine should remain in the system (Iwamoto and Klaassen, 1977). Such enhanced aversion is thought to reflect the negative motivational and affective state associated with morphine withdrawal (Gracy et al, 2001;Mucha and Walker, 1987) and may be a product of the counteradaptive processes that lead to dysregulation of hedonic homeostasis (Kreek and Koob, 1998). As important as this may be to compulsive drug seeking and addiction (Kreek and Koob, 1998), the mechanisms underlying the increase in naloxone CPA after morphine pretreatment are unknown.…”
Section: Introductionmentioning
confidence: 99%